Molecular sieve DNL-14 as well as preparation method and application thereof

By designing aluminum phosphate or aluminum silicon phosphate molecular sieve DNL-14 with a three-dimensional 8*8*20-member ring pore structure, the problem of super-large pore molecular sieve is relatively rare in existing aluminum phosphate molecular sieves, and the synthesis of new framework structures is achieved, enriching the structure type and improving the application possibility.

CN119660759AActive Publication Date: 2025-03-21DALIAN INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202311225950.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-21
Publication Date
2025-03-21
Estimated Expiration
2043-09-21

AI Technical Summary

Technical Problem

Ultra-large pore molecular sieve is rare among existing phosphorus aluminum molecular sieves, and the pore structure type is relatively single, making it difficult to meet the needs of complex applications.

Method used

Aluminum phosphate or aluminum silicon phosphate molecular sieve DNL-14 with a three-dimensional 8*8*20-membered ring channel structure was designed. The synthesis of a new framework structure was achieved by reasonably selecting the organic template agent 1,8-bisdimethylaminonaphthalene and controlling the crystallization conditions.

Benefits of technology

A new type of molecular sieve with a framework structure was successfully synthesized, which enriched the structural types of aluminum phosphate molecular sieve, provided a wider application possibility, and the synthesis process was simple and operational.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119660759A_ABST
    Figure CN119660759A_ABST
Patent Text Reader

Abstract

The invention discloses a molecular sieve DNL-14 and a preparation method thereof, and belongs to the technical field of molecular sieves. The chemical composition of the molecular sieve DNL-14 is (Si < x > P < 48-x > Al < 48 > O < 192 >). 8R. YH < 2 > O < x > is the mole number of Si in each mole of Si < x > P < 48-x > Al < 48 > O < 192 >, x is equal to 0-2.0, y is the mole number of H < 2 > O in each mole of Si < x > P < 48-x > Al < 48 > O < 192 >, and y is equal to 0-10.0; r is an organic template agent 1, 8-bis (dimethylamino) naphthalene; the molecular sieve has a three-dimensional 8 * 8 * 20-membered ring pore channel structure, is a tetragonal crystal system and belongs to an I4 space group; particles of the molecular sieve are rod-shaped, and the length is 1-2mm. The invention synthesizes the silicoaluminophosphate molecular sieve with a novel skeleton structure, and the silicoaluminophosphate molecular sieve can be used for adsorption separation and has relatively high water adsorbability; the synthesis process is simple, and the operability is high.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of molecular sieves, and in particular relates to a molecular sieve DNL-14 and a preparation method and application thereof. Background Art

[0002] Molecular sieve is a porous material with regular pores or cage-like structures. According to the type of elements, it can be divided into silicon-aluminum molecular sieve, phosphorus-aluminum molecular sieve, silicon-germanium molecular sieve, etc. The complex and diverse pore structure also makes molecular sieve play an important role in adsorption separation, industrial catalysis and other fields.

[0003] According to the size of the pores, molecular sieve materials can be divided into small pore, medium pore, large pore and ultra-large pore molecular sieves, corresponding to windows with less than 8-membered rings, less than 10-membered rings, less than 12-membered rings and more than 12-membered rings. According to the pore dimension, molecular sieve materials can be divided into one-dimensional, two-dimensional and three-dimensional materials. Different pore dimensions and sizes also determine the application of this material in adsorption separation.

[0004] At present, super large pore molecular sieves are still relatively rare in the phosphorus aluminum molecular sieve system. In recent years, researchers have made great breakthroughs in the field of phosphorus aluminum molecular sieves in terms of new material pores, such as the earliest VFI molecular sieve (18 rings), followed by IFO (16 rings) molecular sieve, and DNL-1 (20 rings) molecular sieve. DNL-1 is the phosphorus aluminum molecular sieve with the largest number of pore rings so far. Summary of the invention

[0005] In view of this, the present invention provides a molecular sieve DNL-14 and a preparation method and application thereof. The main purpose is to develop a molecular sieve with a three-dimensional 8*8*20-membered ring channel structure. The molecular sieve is a medium-porous molecular sieve material of aluminum phosphate or silicoaluminophosphate, which enriches the structural types of aluminum phosphate molecular sieves.

[0006] On the one hand, the present invention provides a molecular sieve DNL-14, the chemical composition of the molecular sieve is

[0007] (Si x P 48-x Al 48 O 192 ).8R.yH 2 O formula I;

[0008] In formula I, x is x P 48-x Al 48 O 192 The molar number of Si in the solution, x = 0 to 2.0,

[0009] y is per mole of Si x P 48-x Al48 O 192 Medium H 2 The number of moles of O, y = 0 to 10.0;

[0010] R is an organic template having a structure shown in Formula II;

[0011]

[0012] Optionally, x is selected from any value of 0, 0.5, 1.0, 1.5, 2.0, or any range therebetween.

[0013] Optionally, y is selected from any value of 0, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10 or any range therebetween.

[0014] Optionally, the molecular sieve has a three-dimensional 8*8*20-membered ring channel structure.

[0015] In the present invention, three-dimensional 8*8*20 means having an 8-membered ring, an 8-membered ring and a 20-membered ring in a three-dimensional direction.

[0016] Optionally, the molecular sieve is a tetragonal crystal system and belongs to the I4 space group.

[0017] Optionally, the unit cell parameters are

[0018] Optionally, the molecular sieve particles are in the shape of long strips (strip-shaped rectangular parallelepiped) with a length of 1 to 2 mm.

[0019] Optionally, the X-ray powder diffraction of the molecular sieve has diffraction peaks at least at the following positions;

[0020]

[0021]

[0022] In a second aspect, the present invention provides a method for preparing the molecular sieve DNL-14, the preparation method comprising the following steps:

[0023] S1: raw materials containing phosphorus source, aluminum source, silicon source, organic template, mineralizer, water and solvent are mixed to obtain reaction gel;

[0024] S2: The reaction gel is heated and crystallized under closed conditions to obtain molecular sieve raw powder.

[0025] Optionally, in step S1, the molar ratio of the organic template, the phosphorus source, the alcohol solvent, the mineralizer, the aluminum source, the silicon source and the water in the reaction gel is:

[0026] aR:bH 3 PO 4:cROH:d:HF:q Al 2 O 3 :mSiO 2 :nH 2 O;

[0027] Wherein, a=1-10.0, the mole number of the organic template is the mole number of itself;

[0028] b = 0.5 ~ 2.0, the molar number of phosphorus source is expressed as H 3 PO 4 The number of moles;

[0029] c = 20 to 60.0, the mole number of the alcohol solvent is calculated based on the mole number of its own ROH;

[0030] d = 1.0-6.0, the mole number of the mineralizer is based on the mole number of HF;

[0031] q = 0.1 ~ 1.2, the molar number of aluminum source is Al 2 O 3 The number of moles;

[0032] m=0~1.0, the molar number of silicon source is SiO 2 The number of moles;

[0033] n = 5 to 30, the number of moles of water is expressed in H 2 The number of moles of O is measured.

[0034] Optionally, a is selected from any value of 1, 2, 3, 4, 5, 6, 7, 8, 9, 10 or a range of values ​​between any two thereof.

[0035] Optionally, b is selected from any value among 0.5, 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.8, 2.0 or any range therebetween.

[0036] Optionally, c is independently selected from any value among 20, 25, 30, 35, 40, 45, 50, 55, 60, or any range therebetween.

[0037] Optionally, d is independently selected from any value of 1, 2, 3, 4, 5, 6, or a range of values ​​therebetween.

[0038] Optionally, q is independently selected from any value among 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, or any range therebetween.

[0039] Optionally, m is independently selected from any value among 0, 0.1, 0.15, 0.2, 0.3, 0.5, 0.6, 0.8, 0.9, 1.0 or any range therebetween.

[0040] Optionally, n is independently selected from any value of 5.0, 6.0, 7.0, 8.0, 9.0, 10.0, 20.0, 30.0, or any range therebetween.

[0041] Optionally, the organic template is 1,8-bis(dimethylaminonaphthalene).

[0042] Optionally, the alcohol solvent is selected from at least one of cyclohexanol, ethylene glycol, diethylene glycol and triethylene glycol; preferably triethylene glycol.

[0043] Optionally, the mineralizer is a compound containing fluoride ions.

[0044] Optionally, the phosphorus source is selected from phosphoric acid and / or phosphorus pentoxide.

[0045] Optionally, the aluminum source is selected from at least one of pseudo-boehmite, aluminum hydroxide and aluminum isopropoxide.

[0046] Optionally, the silicon source is selected from at least one of silica sol, ethyl orthosilicate, tetramethoxysilane and white carbon black.

[0047] Optionally, in step S2, the crystallization temperature is 80 to 240° C., and the crystallization time is 1 to 60 days.

[0048] Optionally, the crystallization temperature is independently selected from any value among 80°C, 90°C, 100°C, 110°C, 120°C, 130°C, 140°C, 150°C, 160°C, 170°C, 180°C, 190°C, 200°C, 210°C, 220°C, 230°C, 240°C or any range between two thereof.

[0049] Optionally, the crystallization time is independently selected from any value among 1d, 5d, 10d, 15d, 20d, 25d, 30d, 35d, 40d, 45d, 50d, 55d, 60d, or any range between two of them.

[0050] Optionally, in step S1, the phosphorus source and the solvent are mixed, and then an aluminum source is added, and then an organic template is added to obtain an initial gel mixture, and then hydrofluoric acid is added, and the mixture is stirred and mixed at 500 rpm to obtain the reaction gel.

[0051] Optionally, the molecular sieve raw powder is calcined to remove the template agent to obtain the molecular sieve DNL-14; the calcination temperature is 500-600° C., and the calcination time is 3-5 hours.

[0052] Optionally, in step S2, the crystallized product is washed and dried to obtain the molecular sieve raw powder.

[0053] Optionally, the crystallization is carried out in a stainless steel high-pressure reactor.

[0054] Optionally, the drying is carried out in air at 90-110°C.

[0055] The present invention designs the reaction ratio of each component and selects a specific organic template 1,8-bis(dimethylaminonaphthalene) to obtain a three-dimensional 8*8*20-membered ring channel new structure silicoaluminophosphate molecular sieve DNL-14 under reasonable crystallization conditions.

[0056] Compared with the prior art, the present invention has the following beneficial effects:

[0057] 1) The present invention synthesizes a molecular sieve with a novel framework structure.

[0058] 2) The preparation method provided by the present invention has a simple synthesis process and strong operability. BRIEF DESCRIPTION OF THE DRAWINGS

[0059] Figure 1 is the X-ray powder diffraction pattern (XRD) of the product obtained in Example 1 of the present invention;

[0060] Figure 2 It is a scanning electron microscope image (SEM) of the product obtained in Example 1 of the present invention. DETAILED DESCRIPTION

[0061] The present application is further described below in conjunction with specific embodiments. The following are only a few embodiments of the present application, and are not intended to limit the present application in any form. Although the present application discloses the following preferred embodiments, they are not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the above disclosed technical content to make some changes or modifications are equivalent to equivalent implementation cases and are within the scope of the technical solution.

[0062] Unless otherwise specified, the raw materials in the examples of the present application were purchased from commercial sources and used directly without any special treatment.

[0063] The analysis method in the examples of this application is as follows:

[0064] The sample phase analysis was carried out by X-ray powder diffraction (XRD) analysis. The instrument used was an X'Pert PRO X-ray diffractometer from PANalytical of the Netherlands, using a Cu target and a Kα light source. Tested under 40KV voltage and 40mA current.

[0065] The composition of the samples was determined by X-ray fluorescence spectroscopy (XRF) analysis using a Magix-601 X-ray fluorescence spectrometer from Philips.

[0066] The sample morphology was analyzed by scanning electron microscopy (SEM), and the instrument used was: Hitachi SU8020 field emission scanning electron microscope.

[0067] The samples were thermally analyzed using a TAQ-600 thermal analyzer at a heating rate of 10°C / min from room temperature to 900°C.

[0068] cRED data were collected on a JEOL 2100Plus transmission electron microscope equipped with an EMSIS GmbH camera and an ASI Cheetah120 detector.

[0069] Example 1 Preparation of Sample 1

[0070] 0.538g of orthophosphoric acid (85%) was added to 10.38g of triethylene glycol (99%) and mixed and stirred, then 0.951g of aluminum isopropoxide (98%) was added and stirred until uniform, then 1.497g of 1,8-bis(dimethylaminonaphthalene) (98%) was added and stirred vigorously (500rpm) to mix uniformly to obtain an initial gel mixture; then 0.38g of hydrofluoric acid (40%) was added. The mixture was transferred to a stainless steel autoclave and statically crystallized at 200°C for 72 hours under autogenous pressure. After the crystallization was completed, the solid product was centrifuged, washed, and dried in air at 100°C to obtain a white powder product.

[0071] The product was confirmed to be DNL-14 by X-ray powder diffraction, and was recorded as sample 1. The X-ray powder diffraction pattern (XRD) of sample 1 is as follows: Figure 1 As shown in the scanning electron microscope (SEM) Figure 2 As shown, the particles of sample 1 are rectangular parallelepiped with a length of 1 mm to 2 mm. At the same time, the morphology of the molecular sieve in the SEM image is uniform, and the synthesized molecular sieve does not contain other phases, reflecting the high purity of the molecular sieve. The elemental composition of sample 1 obtained by XRF analysis and thermal analysis normalization is: (P 48 Al 48 O 192 ).8R, wherein R is 1,8-bis(dimethylaminonaphthalene).

[0072] Table 1. X-ray powder diffraction characteristics of sample 1

[0073]

[0074]

[0075]

[0076] Example 2 Preparation of Sample 2

[0077] 0.539g of orthophosphoric acid (85%) was added to 10.399g of triethylene glycol (99%) and mixed and stirred. Then 0.949g of aluminum isopropoxide (98%) was added and stirred until uniform. Then 2.996g of 1,8-bisdimethylaminonaphthalene (98%) was added and stirred vigorously (500rpm) to mix uniformly to obtain an initial gel mixture. Then 0.686g of hydrofluoric acid (40%) was added. The mixture was transferred to a stainless steel autoclave and statically crystallized at 200°C for 72 hours under autogenous pressure. After the crystallization was completed, the solid product was centrifuged, washed, and dried in air at 100°C to obtain a white powder product. The product was confirmed to have DNL-14 by X-ray powder diffraction and was recorded as sample 2. The scanning electron microscope photo (SEM) of sample 2 was similar to that of sample 1.

[0078] Example 3 Preparation of Sample 3

[0079] 0.541g of orthophosphoric acid (85%) was added to 13.432g of tetraethylene glycol (99%) and mixed and stirred. Then 0.954g of aluminum isopropoxide (98%) was added and stirred until uniform. Then 1.498g of 1,8-bis(dimethylaminonaphthalene) (98%) was added and stirred vigorously (500rpm) to mix uniformly to obtain an initial gel mixture. Then 0.344g of hydrofluoric acid (40%) was added. The mixture was transferred to a stainless steel autoclave and statically crystallized at 200°C for 72 hours under autogenous pressure. After the crystallization was completed, the solid product was centrifuged, washed, and dried in air at 100°C to obtain a white powder product. The product was confirmed to have DNL-14 by X-ray powder diffraction and was recorded as sample 3. The scanning electron microscope photo (SEM) of sample 3 was similar to that of sample 1.

[0080] Example 4 Preparation of Sample 4

[0081] 0.533g of orthophosphoric acid (85%) was added to 10.39g of tetraethylene glycol (99%) and mixed and stirred. Then 0.952g of aluminum isopropoxide (98%) was added, and then 0.066g of silica sol (60.08%) was added and stirred until uniform. Then 3g of 1,8-bisdimethylaminonaphthalene (98%) was added and stirred vigorously (500rpm) to mix uniformly to obtain an initial gel mixture. Then 0.683g of hydrofluoric acid (40%) was added. The mixture was transferred to a stainless steel autoclave and statically crystallized at 200°C for 72 hours under autogenous pressure. After the crystallization was completed, the solid product was centrifuged, washed, and dried in air at 100°C to obtain a white powder product. The product was confirmed to have DNL-14 by X-ray powder diffraction and was recorded as sample 4. The scanning electron microscope photo (SEM) of sample 4 was similar to that of sample 1.

[0082] Example 5 Structural Analysis

[0083] Continuous rotation electron diffraction (cRED) tests were performed on samples 1-4. The structural analysis results showed that DNL-14 crystallized in the tetragonal system with an I4 space group. The unit cell parameters obtained by structural refinement were The framework information of the molecular sieve can be obtained.

[0084] The above are only a few embodiments of the present application and do not constitute any form of limitation to the present application. Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the technical content disclosed above to make slight changes or modifications are equivalent to equivalent implementation cases and fall within the scope of the technical solution.

Claims

1. A molecular sieve DNL-14, characterized in that: The chemical composition of the molecular sieve is (Si x P 48-x Al 48 O 192 ).8R.yH2O of formula I; In formula I, x is x P 48-x Al 48 O 192 The number of moles of Si in the solution, x = 0 to 2.0, y is per mole of Si x P 48-x Al 48 O 192 The number of moles of H2O in the solution, y = 0 to 10.0; R is an organic template having a structure shown in Formula II; 2. According to the molecular sieve DNL-14 described in claim 1, characterized in that: The molecular sieve has a three-dimensional 8*8*20-membered ring channel structure; The molecular sieve is a tetragonal system and belongs to the I4 space group; The unit cell parameters are The molecular sieve particles are in the shape of long strips, with a length of 1 to 2 mm.

3. According to the molecular sieve DNL-14 described in claim 1, characterized in that: The X-ray powder diffraction of the molecular sieve has diffraction peaks at least at the following positions; 4. The method for preparing a molecular sieve DNL-14 according to any one of claims 1 to 3, characterized in that: The preparation method comprises the following steps: S1: raw materials containing phosphorus source, aluminum source, silicon source, organic template, mineralizer, water and solvent are mixed to obtain reaction gel; S2: The reaction gel is heated and crystallized under closed conditions to obtain molecular sieve raw powder.

5. The method for preparing molecular sieve DNL-14 according to claim 4, characterized in that: In step S1, the molar ratio of the organic template, phosphorus source, alcohol solvent, mineralizer, aluminum source, silicon source and water in the reaction gel is: aR: bH3PO4: cROH: d: HF: q Al2O3: m SiO2: nH2O; Wherein, a=1-10.0, the mole number of the organic template is the mole number of itself; b = 0.5-2.0, the mole number of phosphorus source is calculated as the mole number of H3PO4; c = 20 to 60.0, the mole number of the alcohol solvent is calculated based on the mole number of its own ROH; d = 1.0-6.0, the mole number of the mineralizer is based on the mole number of HF; q = 0.1 to 1.2, the molar number of the aluminum source is calculated as the molar number of Al2O3; m = 0 to 1.0, the mole number of the silicon source is based on the mole number of SiO2; n=5-30, the molar number of water is calculated as the molar number of H2O.

6. The method for preparing molecular sieve DNL-14 according to claim 4, characterized in that: The organic template is 1,8-bis(dimethylaminonaphthalene); The alcohol solvent is selected from at least one of cyclohexanol, ethylene glycol, diethylene glycol and triethylene glycol. The mineralizer is a compound containing fluoride ions.

7. The method for preparing molecular sieve DNL-14 according to claim 4, characterized in that: The phosphorus source is selected from phosphoric acid and / or phosphorus pentoxide; The aluminum source is selected from at least one of pseudo-boehmite, aluminum hydroxide and aluminum isopropoxide; The silicon source is selected from at least one of silica sol, ethyl orthosilicate, tetramethoxysilane and white carbon black.

8. The method for preparing molecular sieve DNL-14 according to claim 4, characterized in that: In step S2, the crystallization temperature is 80 to 240° C., and the crystallization time is 1 to 60 days; Preferably, in step S1, the phosphorus source and the solvent are mixed, and then an aluminum source is added, and then an organic template is added, and then hydrofluoric acid is added, and the mixture is stirred and mixed at 500 rpm to obtain the reaction gel.

9. Use of the molecular sieve DNL-14 according to any one of claims 1 to 3 in adsorption separation.

10. A water adsorbent, characterized in that: The material of the water adsorbent includes the molecular sieve DNL-14 described in any one of claims 1 to 3.

Citation Information

Patent Citations

  • -CLO structural aluminum phosphate molecular sieve and preparation method thereof

    CN102139885A

  • Synthesis method of silicoaluminophosphate molecular sieve with AFO structure

    CN102139889A

  • Method of synthesizing super large micropore aluminium phosphate molecular sieve in eutectic mixture

    CN102476806A

  • Aluminophosphate molecular sieve with -CLO structure and preparation method thereof

    WO2011091678A1